Physically Crosslinked Poly (Vinyl Alcohol)/Kappa-Carrageenan Hydrogels: Structure and Applications - Croitoru, Catalin (Polymers (Basel), 2020)
This paper discusses the structure morphology and the thermal and swelling behavior of physically crosslinked hydrogels, obtained from applying four successive freezing–thawing cycles to poly (vinyl alcohol) blended with various amounts of κ-carrageenan. The addition of carrageenan in a weight ratio of 0.5 determines a twofold increase in the swelling degree and the early diffusion coefficients of the hydrogels when immersed in distilled water, due to a decrease in the crystallinity of the polymer matrix. The diffusion of water into the polymer matrix could be considered as a relaxation-controlled transport (anomalous diffusion). The presence of the sulfate groups determines an increased affinity of the hydrogels towards crystal violet cationic dye. A maximum physisorption capacity of up to 121.4 mg/g for this dye was attained at equilibrium.